A hybrid infrastructure for surveillance-based sensor network experiments - Biswas, P.K.; Phoha, S. (2nd International Conference on Testbeds and Research Infrastructures for the Development of Networks and Communities, 2006. TRIDENTCOM 2006, 2006)
In this paper, we describe a distributed sensor network test-bed and a surveillance experiment, as a technical solution to our sensor network challenge problem, to demonstrate the integration of distributed tracking algorithms with strategies for location estimation, energy management and mobility management of sensor nodes. The infrastructure for the test-bed provides an integrated platform consisting of real sensor nodes augmented with a simulated environment. It consists of several static and mobile physical sensor nodes, fixed sensors, virtual sensor nodes (sensing, tracking and communicating processes) and a network simulator that can simulate a sensor network. Data from real world tracking is provided instantaneously to the simulated environment, where it is used, analyzed and refined through various surveillance algorithms. Results from these simulations are then fed back to the real world to enable the sensor network to reorganize for reinforced tracking. The results indicate that a large number of distributed and interacting sensor nodes, with different capabilities and operating in different environments, can be incorporated in high fidelity experiments to analyze the challenging aspects of the surveillance problem through realistic application scenarios